Pengaruh Motivasi Minat Dan Pengetahuan Mahasiwa Akuntansi Terhadap Memilih Konsentrasi Akuntansi Manajemen - Zulia Hanum (Jurnal Riset Akuntansi dan Bisnis, 2021)
This study aims to determine: (1) The effect of student interest motivation on choosing a management accounting concentration at the Muhammadiyah University of North Sumatra. (2) the influence of students' knowledge about choosing a concentration in Management Accounting at the Faculty of Economics and Business, University of Muhammadiyah North Sumatra. (3) The effect of exploring the factors that influence the selection of accounting study programs in the fifth and seventh semesters at private and public universities in Medan. With this research, the type of research used is qualitative research. The population of this research is 2,181,326 students of Muhammadiyah University of North Sumatra and a sample of 87 students. This study uses data normality test, multicollinearity test, and heteroscedasticity test for classical assumption test and multiple linear regression analysis for hypothesis testing. The results of this study indicate that the motivation of students' interest in knowledge has an effect on choosing a management accounting concentration at the Muhammadiyah University of North Sumatra, Faculty of Economics and Business.